Guided Inquiry Method: Upaya Meningkatkan Hasil Belajar IPA Siswa Kelas VII MTs Negeri 4 Gunungkidul Tahun Pelajaran 2018/2019 - Isfi Muzari (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2019)
This study aims to improve the learning outcomes of class VII students of MTs N 4 Gunungkidul in the academic year 2018/2019 with the application of Guided Inquiry models in Pollution material in Gunungkidul 4 MTs. This research is a Research Action class. The results of the research in the first cycle and second cycle showed an increase in student learning outcomes. Assessment results on student learning outcomes are as follows, cycle I: observation of attitudes of students on average 2.72 with good criteria and completeness 64.29%, while for students' skills the average value is 68.57 with sufficient criteria and completeness 60, 71%, while for the average knowledge the value is 54.76 with fewer criteria and completeness of 42.9%. Cycle II: the results of attitude observation averaged 2.8 with good criteria and completeness 75%, while for the observation of skills students averaged 73.21 with sufficient criteria and completeness 82.1%, while for knowledge the average value 68.10 with sufficient criteria and completeness of 78.6%. Based on the observational data of students' attitudes and skills as well as the results of the test, it can be concluded that the science learning outcomes of class VII C MTs N 4 Gunungkidul students through the implementation of Guided Inquiry learning models have increased.